Soft law in the French public administration - BARREIX, Claude (Advances in Social Sciences Research Journal, 2015)
France is traditionally the country of hard law and is known for having voted or decided and implemented a lot of laws and regulations often setting up complex and excessive standards in various fields related to economic, social and even personal life of its citizens. In principle, the French seem opposed to relationships ruled by soft law as contracts or agreements. The purpose of this article is to try to show that even if their culture leads them to mistrust soft law, the French have been for a long time using this legal instrument, particularly in public administration. The movement has been developed since the 1990’s mainly concerning framework contracts with the unions, internal contracts and charters. A development of soft law, now approved by the ‘Conseil d’Etat’ (the French highest level of the administrative jurisdiction) would participate to simplify and diminish excessive standards and contribute to add value to the image of France as a modern state.